Myocardial perfusion in patients with diabetes mellitus according to stress CMR with adenosine triphosphate - A. I. Pivovarova; G. N. Soboleva; O. V. Stukalova; S. K. Ternovoy (Евразийский Кардиологический Журнал)
Aim. To evaluate the features of myocardial perfusion according to stress CMR with adenosine triphosphate (ATP) in patients with type 2 diabetes mellitus (DM) and obstructive and non-obstructive coronary arteries (CA).Materials and Methods. Stress СMR with ATP was provided in 55 patients with a suspected or known ischemic heart disease. 39 patients of them had DM type 2. All patients were provided with invasive coronary angiography or non-invasive CT angiogram to evaluate lesions of CA. Study protocol included providing myocardial perfusion in a rest and stress with ATP in dose 160 mkg/ kg/min during 3-6 min.Results. The detection of stress-induced perfusion defects was statistically significantly associated with the obstructive CA lesions of more than 50% (p<0,001). With non-obstructive CA lesions less than 50%, perfusion defects were found more often in patients with DM (36.4%) than in patients without DM (16.7%). Furthermore, the detection of stress-induced myocardial ischemia of patients with DM was not statistically significantly associated with obstructive CA (p=0,071) In case of positive result of stress CMR, patients with DM had a more widespread zone of stress-induced ischemia in the form of increase involved segments (6,45±3,78 (4,78-8,13) than patients without DM (3,17±1,60 (1,49-4,85), p=0,050).Conclusion. Patients with DM and non-obstructive CA are more likely to have a myocardial perfusion disorder than patients without DM due to coronary microvascular dysfunction.